Pelatihan Pembuatan Game Edukasi Berbasis Android Berbantuan RPG Maker bagi Siswa SMA Islam Al-Azhar 5 Cirebon - Muchammad Subali Noto; Surya Amami Pramuditya; Setiyani Setiyani (PERDIKAN (Journal of Community Engagement), 2020)
Almost everyone has a smartphone, including students. The potential for open application development on Android and the increasing number of people using smartphones allow them to use technology to support activities in the world of education, one of which is mobile learning. Educational games are a part of mobile learning. The purpose of the Community Service (PKM) activity is to improve students' abilities in utilizing technology through training in Android-based educational games assisted by RPG Maker. Through the making of this educational game, students can develop an interest in IT and learn mathematics. Participants in the PKM activities were students of Al-Azhar 5 Islamic High School Cirebon City who became the KIR community members. This service method consisted of three stages, namely preparation, implementation of training, and evaluation. The indicators of this activity's achievement include students being able to make maps, prologues, bring up avatars, create questions, create dialogues, battle, move one character from one map to another, and deploy games successfully controlled by participants. During the training, the participants were very enthusiastic in listening to the material and were active in making educational games.(Hampir setiap orang memiliki smartphone termasuk pelajar. Potensi pengembangan aplikasi yang terbuka pada Android dan semakin banyaknya masyarakat yang menggunakan smartphone, membuka peluang teknologi ini dapat digunakan untuk mendukung aktivitas dalam dunia pendidikan salah satunya adalah mobile learning. Game edukasi merupakan salah satu bagian dari mobile learning. Tujuan dari kegiatan Pengabdian Kepada Masyarat (PKM) adalah untuk meningkatkan kemampuan siswa dalam memanfaatkan teknologi melalui pelatihan game edukasi berbasis Android berbantuan RPG Maker. Melalui pembuatan game edukasi ini, siswa dapat mengembangkan minat di bidang IT sekaligus belajar matematika. Peserta dalam kegiatan PKM adalah siswa SMA Islam Al-Azhar 5 Kota Cirebon yang tergabung dalam komunitas KIR. Metode dalam pengabdian ini terdiri dari tiga tahap yaitu persiapan, pelaksanaan pelatihan, dan evaluasi. Indikator ketercapaian kegiatan ini diantaranya siswa mampu membuat map, prolog, memunculkan avatar, membuat soal, membuat dialog, battle, memindahkan satu tokoh dari map satu ke map yang lain, serta mendeploy game berhasil dikuasai oleh peserta. Selama pelatihan berlangsung, peserta sangat antusias dalam menyimak materi dan aktif dalam pembuatan game edukasi).